Risk of endometrial cancer in patients with a preoperative diagnosis of atypical endometrial hyperplasia treated with total laparoscopic hysterectomy - Katsutoshi Oda; Kaori Koga; Tetsuya Hirata; Masanori Maruyama; Masako Ikemura; Yoko Matsumoto; Kazunori Nagasaka; Katsuyuki Adachi; Mayuyo Mori-Uchino; Kenbun Sone; Takahide Arimoto; Osamu Wada-Hiraike; et al. (Wolters Kluwer Medknow Publications, 2016)
Objective: Distinguishing atypical endometrial hyperplasia (AEH) and endometrial cancer (EC) is often difficult, and patients with a preoperative diagnosis of AEH are sometimes diagnosed with EC after hysterectomy. In this study, we assessed the risk factors for EC in patients who underwent total laparoscopic hysterectomy (TLH) with a preoperative diagnosis of AEH. Patients and methods: We retrospectively analyzed 20 patients with a preoperative diagnosis of AEH using endometrial cytology, biopsy (fractional and total curettage), and hysteroscopic inspection. Results: Four of 20 (20%) patients were diagnosed with EC after TLH, all of whom had endometrioid adenocarcinoma Grade 1 and Stage IA without lymph node metastasis. Four of seven (57%) patients who were highly suspected of having EC by three diagnostic modalities (cytology, fractional curettage, and by hysteroscopy) were diagnosed with EC after TLH, whereas none of the 13 without any suspicious findings in these examinations were diagnosed with EC (p=0.007 by Fisher's exact test). Hysteroscopic findings were positive (suspicious of EC) in six of 11 patients tested, including all four EC patients. However, either endometrial cytology or fractional curettage alone failed to predict cancer in two EC patients. All four EC patients were also suspected of having EC by total curettage. Ovarian preservation was performed in 12 (60%) patients. Three of the four EC patients received subsequent surgery, including pelvic lymphadenectomy. Conclusion: Careful preoperative examinations, including hysteroscopy, might be useful to evaluate the risk of EC. Accordingly, we should be still careful about the possibility of overdiagnosis in patients with AEH.